If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + -9y = 0 Combine like terms: 15y + -9y = 6y 6y = 0 Solving 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '6'. y = 0 Simplifying y = 0
| -3-y=6 | | (40x)+(100y)=2500000 | | 2x+9=13+2x | | 15-2y/4=3 | | 2.5n-14=-12.25 | | 56-21x=-4x+29 | | 4x-8=9x+3 | | 2x-5x-7=-14 | | x+-10=12 | | -12x+10+17x-7=12+4x-2+x | | P+7=32 | | -4.9x^2-8x-30=0 | | 3a^3b-24b^4=0 | | 6k+3w-w+5k= | | 2.3x=47 | | 3m+5n=6m-2n | | 5(2)+15x=10 | | 21x^2-6x+13=0 | | x^2+9y^2=28 | | 3x+2-x-5=7x+6-4x-2 | | -6(2t+10)=-24 | | 3(4x+1)=5x-8x | | .5b^2=16 | | 5(3s+7)=185 | | 2(f-8)=-2 | | 9x-94=116-5x | | 5w+16=66 | | .5b^2-81=0 | | 1.3x=-13 | | -3x+17+5x-7=-5x+2+7x-10 | | 3x+10=33+2x | | 0.5-3-x=6.5 |